Analisis Perbandingan Keamanan Data pada Website Repository UNHI dan Website SRUTI UNHI Terhadap Sniffing Process Menggunakan Aplikasi Wireshark - Bayu Suputra, I Made Ramanda; Asmarajaya, I Kadek Andy; Adi Jaya, I Kadek Noppi (RESI : Jurnal Riset Sistem Informasi, 2025)
The rapid development of information technology has increased the risk of data security in computer networks, especially through information sniffing. Universitas Hindu Indonesia (UNHI) has two web platforms, Repository UNHI and SRUTI UNHI, which use different protocols (HTTP and HTTPS). This research analyzes and compares data security on both websites against sniffing attacks using the Wireshark application and provides insights into the vulnerabilities of the HTTP protocol and the advantages of the HTTPS protocol. This research uses a descriptive method with a qualitative approach applied through the Network Development Life Cycle (NDLC). Wireshark is used to capture and analyze data packets on the network of both websites. The analysis results show that the Repository UNHI website, which uses HTTP, is highly vulnerable to sniffing attacks, with Wireshark successfully Capturing and reading sensitive data such as usernames and passwords. Conversely, the SRUTI UNHI website, which uses HTTPS, demonstrates a higher level of security as the data transmitted is encrypted. This research indicates that the use of the HTTPS protocol significantly enhances data security compared to HTTP